Eleventh Five Year Plan (2007-2012) and Annual Plan 2007-08 Draft Proposals Volume - I General Presentation and Sectoral Programmes - Planning Commission (Planning Commission, 2007)
We propose rapid industralisation to improve employment and income, taking advantage of the North East Industrial Policy. We are also encouraging heavy industries especially cement plants and ferrous and nonferrous industries with captive power generation. We have also taken up with the( Department of Industrial Policy and Promotion (DIPP). Government of India, to extend the financial assistance to power plants also under the North East Industrial Policy. Agriculture and its allied activities is our priority area for improving livelihood of our people, about 70 % of the population being dependent on it.
Planning Department Government of Meghalaya